2019
DOI: 10.1038/s41416-019-0667-3
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and cancer: the future is now

Abstract: In the last decade, the field of cancer metabolism transformed itself from being a description of the metabolic features of cancer cells to become a key component of cellular transformation. Now, the potential role of this field in cancer biology is ready to be unravelled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 16 publications
1
56
0
Order By: Relevance
“…Given our results, we can expand the idea that glycolysis and OXPHOS are present in the same tumor accordingly with subpopulation functionality. So, these results agree that a common feature during cancer progression is metabolic rewiring 44,69 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Given our results, we can expand the idea that glycolysis and OXPHOS are present in the same tumor accordingly with subpopulation functionality. So, these results agree that a common feature during cancer progression is metabolic rewiring 44,69 .…”
Section: Discussionsupporting
confidence: 85%
“…To expand this result, Cluster C cells overexpressed mitochondrial genes that are part of the respiratory complexes (MT-ND3, MT-ATP6, MT-CO2, MT-ND4, MT-CYB, MT-CO3, MT-ND2, MT-CO1, MT-ND5, and MT-RNR1) related to mitochondrial oxidative phosphorylation (OXPHOS). Therefore, these observations suggest a metabolic rewiring among this subpopulation, needed to meet energy demands in the cancer cell 43,44 .…”
Section: Insights Of Functional Heterogeneity To Elucidate the Connementioning
confidence: 87%
“…Speci cally, the highest lifetime cumulative risk of incidence of cancers is lung cancer, the most common type of cancer death in 94 countries, in both high and low HDI (Human Development Index) regions [16]. What's worse, despite many years of efforts, the metabolic reprogramming of cancer cells is far beyond fully understanding and there has been no treatment towards this mechanism in clinical practice [17] due to the complicated feature of aberrant metabolism of cancer. Recently, it has been reported that compared with normal tissues, mRNA levels of SFXN1 was much higher in virtually all kinds of human cancers [15].…”
Section: Discussionmentioning
confidence: 99%
“…HK2 is one of the rate-limited enzymes in glycolysis pathway, and has been recognized to regulate the malignant phenotypes of cancer cells, including cellular apoptosis and migration capabilities [25, -27]. Aerobic glycolysis is the energy metabolism characteristic of tumor cells and fates the malignant phenotype of tumor cells [28][29][30]. Subcutaneous tumor formation in BALB/c nude mice combined with microPET/CT can effectively explore the tumorigenesis and glucose metabolism level of tumors [31].…”
Section: Introductionmentioning
confidence: 99%